Desafio na gestão de pessoas: retenção de servidores na Universidade Federal do Rio Grande do Norte - Gomes, Rainete de Medeiros (2016)
Present research arose from intention to identify the profile of Education Administrative Techinicians of Federal University of Rio Grande do Norte (UFRN) who requested Vacancy by Possession in Another Unaccountable Position and Exoneration, from occupied positions in that Institution between 2010 and 2015. In addition, It sought to understand real reasons that led these people to leave their employment bond considering all the bias that surrounds existing labor relations in the Organization. Bibliographic Review focused on legal documents governing career of the Administrative Techinicians of Federal Institutions of Higher Education (IFES), structure of UFRN and works of authors who have developed studies on this subject, as well as researches on the state of the art. This study concerns a descriptive survey and, in order to achieve its objectives, data collection was performed through the application of an online questionnaire using Google Docs tool to reach surveyed population, which totalized 268 people. 122 questionnaires were responded, and SPSS (Statistical for Social Sciences) was used to treat this information. Main cited reason as dissatisfaction in the Board refers to remuneration inherent to the Career of Administrative Techinicians, represented by the percentage of 91.2% of the answers and, for this reason, one can conclude the understanding for seeking new positions in Public Service, confirmed by the result of 77% of the cases. Based on the data of this study, it is noticed that, in spite of the high index of dissatisfaction with the salary issues, in general, organizational climate and the satisfaction in labor relationships presented a favorable way to researched Institution.